دراسة الأثر التفاعلي للثقافة التنظيمية وجودة نظام المعلومات المحاسبية في المنفعة المدركة لدى مستخدميه - الطويل, ليلى; حمدان, همسه (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف هذا البحث إلى دراسة أثر كلٍ من جودة نظام المعلومات المحاسبية والثقافية التنظيمية السائدة في المنظمات في المنفعة المدركة لنظام المعلومات المحاسبية لدى مستخدميه، وإلى دراسة الأثر التفاعلي لجودة نظام المعلومات المحاسبية مع الثقافة التنظيمية على المنفعة المدركة للنظام لدى مستخدميه. تم جمع بيانات أولية باستخدام استبانة طورت استناداً إلى الدراسات السابقة، ووزعت على عينة غير احتمالية من مستخدمي نظم المعلومات المحاسبية في شركات الملاحة البحرية في سورية. بلغ عدد الاستجابات المقبولة 53 استجابة، حيث خضعت هذه الاستجابات إلى التحليل باستخدام تحليل الانحدار البسيط والمتعدد المعياري والتدريجي. بينت نتائج البحث أن هناك علاقة مباشرة معنوية بين جودة نظام المعلومات المحاسبية ومنفعته المدركة، وكذلك علاقة مباشرة معنوية بين كل من التوجه للموارد البشرية والتعاون والمنفعة المدركة لنظام المعلومات المحاسبية. كما برهنت النتائج على وجود علاقة بين الأثر التفاعلي لجودة النظام مع التوجه للموارد البشرية والتعاون، وبين المنفعة المدركة لنظام المعلومات المحاسبية. The current research aims to study the impact of each of the quality of accounting information system and organizational culture on the users' perceived usefulness, and to study the interactive impact of the organizational culture and the accounting information system quality on the users' perceived usefulness. Primary data were collected using a questionnaire developed using previous studies, and distributed to a non- probability sample of users of accounting information systems in the maritime shipping companies in Syria . 53 acceptable responses were received.Data have been analyzed using linear regression. The results showed that there is a direct significant relationship between the quality of accounting information system and the users' perceived usefulness. They also showed that the dimensions of organizational culture (human resources orientation and cooperation) affect the perceived usefulness directly. The results demonstrated that The interaction between the system quality and each of the human resources orientation dimension and cooperation dimension has an impact on the perceived usefulness of the accounting information system.